Enseñando democracia: normativa, realidad y propuestas en torno a la educación para la ciudadanía en el Perú - Constantino Caycho, Renato (2012)
Teaching democracy: normative, reality and proposalsrelated to education for citizenship in Peru This article aims to review the ethical and political basis of education for citizenship. From the analysis of Peruvian normative it infers the necessity that school produces citizens. Then, it confronts these normativewith the reality of Peruvian school. It also analyses some successful cases, and from this, it formulates proposals made to facilitate the development of a real citizenship in our country.